Sobre Joan Martorell, señor de Beniarbeig, y otros casos de homonimia en el siglo XV valenciano. Notas de archivo y observaciones metodológicas. - VELA, AGUSTÍN RUBIO (Scripta, 2015)
With a methodological purpose, I handle the issue of homonimy in medieval documentation. Identification mistakes, confusions and anachronisms detected in recent studies have contributed to raise awareness about the need to get to know better some onomastic, diplomatic and contextual aspects which allow us to tell the difference between contemporary individuals who had the same surname. The starting point of this article, in which some other cases are also analysed, is the documentation related to Joan Martorell, lord of Beniarbeig, as well as to his son and grandson, three homonymous elements of the same Valencian family living in the 15th century and having blood ties with the author of Tirant lo Blanch.